The Contours of Green Human Resource Development. (November 2015) - Scully-Russ, Ellen
The Problem: Despite growing interest in the role of human resource development (HRD) in creating responsible and sustainable organizations, there is limited discussion on HRD's potential contribution to new interdisciplinary approaches to creating a more sustainable connection between the environment and society, herein called the greening of society . Greening involves an entire community and its stakeholders, and not just the business organizations that garner attention in the HRD literature. The Solution: This article introduces the issue by offering a conceptual framework for understanding HRD's role in greening efforts. The article calls for the development of new HRD concepts, models, and empirical research to help address the mounting environmental challenges and risks to society. It also introduces the articles that launch a preliminary response to this call. The Stakeholders: This article provides scholars, researchers including environmental researchers, and scholar-practitioners with current thinking around the notion of building responsible and sustainable environmental and social sustainability organizations and society. In addition, this article may be of interest to those concerned about environmental and social sustainability.